2006
DOI: 10.1097/01.ccx.0000224872.09077.dc
|View full text |Cite
|
Sign up to set email alerts
|

Venous oximetry

Abstract: Early goal-directed therapy should be implemented in the initial resuscitation of septic patients. Central venous saturation may have prognostic significance following major surgery. Further evaluation of peri-operative trends in central venous saturation is required. Measurement of central venous oxygen saturation can easily be applied in intensive care unit patients and offers a useful, indirect indicator for the adequacy of tissue oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
72
0
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 40 publications
(35 reference statements)
3
72
0
13
Order By: Relevance
“…This led to no apparent measurement different and lead to the finding that both treatments induced increased SvO 2 levels relative to baseline at all-time points, indicating an improvement in cardiovascular performance. [10][11][12] This effect was confirmed by the cardiac index measurements in the GDT patients, monitored through the pulmonary artery catheter.…”
Section: ■ Discussionmentioning
confidence: 55%
“…This led to no apparent measurement different and lead to the finding that both treatments induced increased SvO 2 levels relative to baseline at all-time points, indicating an improvement in cardiovascular performance. [10][11][12] This effect was confirmed by the cardiac index measurements in the GDT patients, monitored through the pulmonary artery catheter.…”
Section: ■ Discussionmentioning
confidence: 55%
“…Increased venous oxygen saturation is thought to be an indicator for reduced oxygen utilization as well as arteriovenous shunting. 29 In normal human physiological conditions, the oxygen saturation of the veins draining their respective organs within the body is highly variable which is thought to reflect variations in the oxygen extraction levels or metabolic activity of the tissues. 30 This is most evident in the renal venules whose oxygen saturation is approximately 92% as a result of relatively low-oxygen extraction in the renal tissues which derives its energy requirements from non-oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that in the early stages of resuscitation of patients with septic shock, a decrease in ScvO 2 is an important manifestation of inadequate tissue perfusion (Marx and Reinhart, 2006). In a retrospective study on the performance of the international guidelines for septic shock treatment (Levy et al, 2010), Levy reported that the hospital mortality in patients with septic shock had decreased from 37 to 30.8% after 3 years of implementation of the guidelines.…”
Section: Discussionmentioning
confidence: 99%